2023
DOI: 10.7759/cureus.37888
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of CAD/CAM (Lithium disilicate and Zirconia) Based and Conventional Full Crowns and Fixed Partial Dentures: A Systematic Review and Meta-Analysis

Abstract: Although CAD/CAM (computer-aided design/computer-aided manufacturing) restorations act as a favorable alternative to conventional metal-ceramic restorations for fixed dental prostheses, little is known about their intermediate and persistent clinical performance. This systematic review and meta-analysis aimed to assess the clinical performance in terms of biological, technical, and esthetic aspects and the survival and success ratios for single full crowns (SFCs) and fixed partial dentures (FPDs) fabricated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Nevertheless, the digital workflow consistently yielded superior outcomes. [6][7][8][9][10] Alternatively, some studies reported the superiority of conventional manual fabrication over CAD/CAM milling technique, in terms of clinical survival, 11 biological, technical, and esthetic complications, 12 and internal fit of the partial coverage restorations. 1 This contrasting evidence does not pertain to the CAD/CAM workflow, as it adheres to standardized protocols and is less reliant on human intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the digital workflow consistently yielded superior outcomes. [6][7][8][9][10] Alternatively, some studies reported the superiority of conventional manual fabrication over CAD/CAM milling technique, in terms of clinical survival, 11 biological, technical, and esthetic complications, 12 and internal fit of the partial coverage restorations. 1 This contrasting evidence does not pertain to the CAD/CAM workflow, as it adheres to standardized protocols and is less reliant on human intervention.…”
Section: Introductionmentioning
confidence: 99%
“…The array of materials available through advanced CAD/CAM systems for producing block-shaped restorative dental materials is remarkable [3,4]. Ceramic-based materials include feldspathic porcelain, leucite-reinforced glass, lithium disilicate glass, and zirconia [5,6]. These ceramics enable the fabrication of all-ceramic crown restorations.…”
Section: Introductionmentioning
confidence: 99%